2010
DOI: 10.1111/j.1537-2995.2009.02414.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased number of coagulation products in relationship to red blood cell products transfused improves mortality in trauma patients

Abstract: In the civilian setting, plasma, PLT, and cryoprecipitate products significantly increased 30-day survival in trauma patients. Future prospective randomized clinical trials are required to determine the optimal transfusion ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
178
0
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(193 citation statements)
references
References 18 publications
4
178
0
11
Order By: Relevance
“…2,109 -111 The survival rate was significantly worse with a low FFP:RBC ratio (i.e., less than 1:2) relative to a high ratio (more than 1:1). 111,112 On the contrary, two other retrospective studies found no benefit of a high FFP:RBC ratio. 113,114 Differences in patient demographics, inclusion criteria, and transfusion protocols may have contributed to these conflicting findings.…”
mentioning
confidence: 78%
“…2,109 -111 The survival rate was significantly worse with a low FFP:RBC ratio (i.e., less than 1:2) relative to a high ratio (more than 1:1). 111,112 On the contrary, two other retrospective studies found no benefit of a high FFP:RBC ratio. 113,114 Differences in patient demographics, inclusion criteria, and transfusion protocols may have contributed to these conflicting findings.…”
mentioning
confidence: 78%
“…Deviation from the 1:1:1 target ratio was also observed in Shaz et al's study involving 132 civilian trauma patients; in that study, the MTP achieved a mean FFP:pRBC ratio of 0.5 and a mean PLT:pRBC ratio of 0.6. (22,23) Evidently, while an ideal transfusion ratio of 1:1:1 may be proposed in MTPs, it has been suggested that this target is not always achievable immediately. Notably, studies have shown that failure to achieve these ratios is associated with higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…-İki puan %38 olasılıkla, 3 puan %45 olasılıkla, 4 puan ise %100 olasılıkla masif transfüzyon gereksinimi olacağına işaret eder. (10,11) . ES:TDP:Plt için 1:1:1 oranını önerenler de mevcuttur (12) .…”
Section: Masif Transfüzyona Gereksinimi Olan Hasta Nasıl Belirlenir?unclassified